The restrained inguinal hernia at children with violation a floor form - M. A. Axel’rov; E. B. Khramova; V. N. Evdokimov; A. V. Shaytarova; A. V. Stolyar (Бюллетень сибирской медицины, 2018)
The most common surgical pathology of childhood, which is necessary for doctors of all specialties, is the inguinal hernia. In the treatment of this pathology, both open procedure and laparoscopic surgery are used. Infringement of a hernia, manifested by sudden or gradual compression of its contents in the gates, is a dangerous complication.Violation of the formation of sex - a condition associated with the clinical and biochemical manifestation of the discrepancy between the genetic, gonadal and phenotypic sex of the child. Traditionally, the term “hermaphroditism” is used to describe this state. A distinction is recognized between true hermaphroditism (gonadal) and false hermaphroditism (the presence of signs opposite to the gonadal sex of the subject). True hermaphroditism is a rare disease. False female hermaphroditism is attributed to conditions in which the female karyotype and gonads that are characteristic of the female sex are determined. But the external genitalia have a bisexual structure. The most common cause of false female hermaphroditism is congenital dysfunction of the adrenal cortex.According to several authors, a frequent cause of amblysexuality of the genitals in newborns is mixed gonadal dysgenesis – a condition in which phenotypic men or women have an egg on one side, and a gonadal cord located either in a wide bundle or on the pelvic wall and consisting from the stroma of the ovary on the other. At birth, the external genitalia are usually the penis, the uro-genital sinus and the labia genitalia, which are intertwined in the scrotum.Evaluation of the patient’s local status with violation of the formation of sex in the occurrence of surgical pathology is not an easy task, since the appearance of the external genitalia in the XX and XY subjects is the same. In 2015, in connection with the injured inguinal hernia in the department of pediatric surgery No. 1, the State Children’s Clinical Hospital “OKB No. 2” in Tyumen received treatment for two children with a violation of the formation of sex. Difficulties in interpreting intraoperative data prompted us to describe these cases.